Embodiment in Evolution and Culture - Etzelmüller, Gregor; Tewes, Christian (Mohr Siebeck, 2016)
From its beginnings, the theory of evolution has unsettled fundamental anthropological assumptions about the place of human beings in nature. The integration of human origins into natural history by Darwinism was countered by the philosophical anthropologies of the 20th century. Their attempts were to hold on even more resolutely to the special status of humans as beings 'open towards the world'. Today, evolutionary and philosophical anthropology have moved closer together via the paradigm of embodiment. Building on embodied cognitive science, this volume aims to establish how far the human mind and human cultural cognition can be attributed to the structures of human existence, structures which have emerged in the course of evolution and have in turn been affected by culture. The traditional dualism of nature and culture is transformed into an explanation of an evolutionary process in which body and mind are understood to be intertwined and mutually constitutive.